AGROINDUSTRY DEVELOPMENT STRATEGY IN KEFAMENANU CITY (CASE STUDY ON SULARSO CRIPS BUSINESS) - Adriana Banunaek; Umbu Joka; Simon Juan Kune (Agribusiness Journal, 2022)
The research on chips business aims to determine the strategy for developing chips (banana and cassava) business in Kefamenanu City. Data analysis method used in this research is descriptive qualitative analysis method, income analysis, SWOT analysis. The sample is the owner of his own business, namely Uncle Sularso. The results showed that the coordinates of 0.16 ; 0.66 were in quadrant I, meaning that the chips (banana and cassava) business was very good to be developed by taking advantage of opportunities and strengths to minimize threats and weaknesses. Through the SWOT matrix obtained 7 strategies in the chips business (bananas and sweet potatoes) that need to be applied in the business, namely improving product quality, increasing production, innovating products, increasing capital, recruiting workers and conducting business licensing in order to obtain business capital and can increase business for develop.